A Study of Women Empowerment: Decision Making and Participation in Farm & Household Economic Activities - M.L. Roy and K.S. Kadian, (Indian Journal of Extension Education, 2016)
Women empowerment especially economic empowerment is very important as it gives security to a woman. It is verycrucial for progress of the society. Women plays a pivotal and potentially benefiting role in all-round growth of resourcepoor farm families. But often they are neglected in decision making on farm and household matters which are mostlymanaged by them. Participation in decision making process especially in economic activities is an indication ofempowerment. The present study attempts to investigate the level of women economic empowerment in resource-poorfarm families by analyzing their extent of participation in decision making on farm and household related economicactivities. The study was conducted in six agro-climatic zones of West Bengal taking a random sample of 120 resourcepoor farm families. Both husband and wife of the families were personally interviewed by pretested structured interviewschedule. Spearman's rank-difference correlation was used to measure the extent of agreement between husband's andwife's responses. The study revealed that wives played a major role to jointly decide purchasing or hiring of land (43.33-47.50 %), selling of produce (35.00-35.83 %) and borrowing for agriculture (26.67-30.00 %). Decisions for milking andprocessing of milk, utilization of dung and sale of milk and milk products were dominantly taken by wives (72.50 per cent,54.67 per cent and 40.83 per cent, respectively), where purchase and sale of animals, type and number of animals to bekept and adoption of new animal husbandry practices were mainly decided jointly (32.50-37.50 per cent, 31.67-36.67 percent and 24.17-27.50 per cent, respectively). Household economic decisions on building new house, householdpurchasing, education of children, selection of occupation for children and financial activities were mainly taken jointly(38.33-41.67 per cent, 32.50-35.83 per cent, 25.00-27.50 per cent, 25.83-30.00 per cent and 24.17-27.50 per cent,respectively). The findings of the study indicated higher level of women economic empowerment in animal husbandryand household sectors.